Maternal Health Education (Pregnant, Childbirth and Postpartum Periods) during the COVID-19 Pandemic: Literature Review - Suryani Manurung (Politeknik Kesehatan Kemenkes RI Jakarta I, 2021)
Maternal is the condition of the mother during pregnancy, childbirth, and puerperal. One of the susceptible individuals infected with COVID-19 is maternal. This condition causes the mother to worry both herself and the baby, so these problems need to be identified and prevented through health education. This article aimed to identify problems and maternal health education (pregnancy, childbirth, and puerperal) during the COVID-19 pandemic. The data collected through an online portal that is PubMed, the Jakarta Health Polytechnic I ProQuest, Google Scholar, and Google-based website. Keywords used to search for information related to the topics discussed are the epidemiology of SARS-COV-2, pregnancy, childbirth, and puerperal during the COVID-19 period, the maternal immune system, complaints, and maternal questions of the COVID-19 pandemic period, and prevention of COVID-19 infection on maternal. The results found a risk of COVID-19 infection in the maternal in the amount of 4.9/1000 pregnant women. Based on COVID-19 infections from nine infected, seven were found dead, and two were surviving. Maternal infection during pregnancy has complications, including fetal distress (2 cases), membrane rupture (2 cases), preeclampsia (1 case), is a factor in preterm labor, mature delivery (1 person). In conclusion, maternal is a high-risk group for exposure to infection. The risk of vertical infection of the mother to the baby has not been proven. Maternal requires information on prevention and care during pregnancy, childbirth, and the puerperal